2017
DOI: 10.1111/jphp.12747
|View full text |Cite
|
Sign up to set email alerts
|

IL-17A blockade or deficiency does not affect progressive renal fibrosis following renal ischaemia reperfusion injury in mice

Abstract: Despite the effects of IL-17 in other inflammation models, neither genetic IL-17A deficiency nor treatment with an IL-17A blocking antibody attenuated IRI and progression to CKD. We conclude that in severe renal IRI IL-17A is not crucially involved in disease progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 40 publications
1
7
0
Order By: Relevance
“…Our finding that IL‐17A deficiency did not reduce renal fibrosis in CKD is, however, compatible with recent data from Thorenz et al . who reported that IL‐17A deficient mice were not protected against renal fibrosis induced by ischaemia/reperfusion injury (Thorenz et al ., ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Our finding that IL‐17A deficiency did not reduce renal fibrosis in CKD is, however, compatible with recent data from Thorenz et al . who reported that IL‐17A deficient mice were not protected against renal fibrosis induced by ischaemia/reperfusion injury (Thorenz et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…For example, cisplatin-induced renal injury was markedly decreased in RAG-1 deficient mice (Nozaki et al, 2011) showing that the adaptive immune system aggravates nephrotoxicity induced by cisplatin. IL-17A producing cells initiate, perpetuate and sustain inflammatory processes by inducing proinflammatory cytokines and chemokines and recruiting other inflammatory cells and orchestrating tissue inflammation (Thorenz et al, 2017). Strikingly, neither deficiency of the adaptive immune system nor of IL-17A affected the induction and course of progressive renal injury.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, some other studies raised doubts due to blockade or deficiency of IL-17A having no beneficial effect on preventing renal fibrosis progression following severe IRI. The different severity of IRI might account for the contradictory conclusions (Thorenz et al, 2017 ; Rosendahl et al, 2019 ). Thus, whether the inhibitors of IL-17 cytokine family can be clinically applicated remains to be explored.…”
Section: Lymphocytes Mediate Aki and Ckd: Diversity And Mechanismsmentioning
confidence: 99%
“…About 70% of the renal tissue was used for leukocyte isolation as described previously. 21 Tissues were homogenized with a gentleMACS dissociator (Miltenyi Biotec, USA) according to the manufacturer's instructions. Digestion with Collagenase II (500 U/ml, Worthington, USA) was performed before and after homogenization for 20 min at 37°C.…”
Section: Flow Cytometry To Estimate Nav13-expressing Neutrophilsmentioning
confidence: 99%